Effects of the water desalting by reverse osmosis on the process of formation of water-alcohol mixtures. 1H NMR spectroscopy studies - Kuzmin, Oleg; Sujkov, Sergey; Niemirich, Oleksandra; Ditrikh, Iryna; Sylka, Iryna (My University, 2017)
Experimentally, using the method of 1H NMR spectroscopy, the influence of the use of reverse osmosis of water treatment on the spectral characteristics of mobile protons of ethanol and water, as well as the stabilization of the system in the process of creation of water-alcohol mixtures, was established.
Keywords: зворотний осмос; етанол; вода; суміш; обратный осмос; этанол; смесь; reverse osmosis; ethanol; water; mixture; кафедра технології ресторанної і аюрведичної продукції